Isolation of intraflagellar transport trains. Issue 8 (7th August 2013) - Mencarelli, Caterina; Mitchell, Aaron; Leoncini, Roberto; Rosenbaum, Joel; Lupetti, Pietro
<x xml:space="preserve">Abstract</x> The intraflagellar transport (IFT) system was first identified in situ by electron microscopy in thin sections of plastic‐embedded flagella as linear arrays of electrondense particles, located between the B tubules of the outer doublets and the flagellar membrane. These arrays of particles are referred to as IFT trains. Upon membrane rupture, IFT trains are thought to easily dissociate to yield soluble IFT particles, which are commonly purified through sucrose gradients as ∼16‐17S complexes. The latters easily dissociate into two subcomplexes, named A and B. We report here the isolation, visualization, and identification by immunolabeling of flexible strings of IFT particles, which are structurally similar to in situ IFT trains and appear to be formed by both complex A and complex B polypeptides. Moreover, the particles forming isolated IFT trains are structurally similar to the individual particles found in the ∼17S gradient peak. Our results provide the first direct evidence that ∼17S particles do indeed compose the IFT trains. The paper also represents the first isolation of the IFT trains, and opens new possibilities for higher resolution studies on their structure and how particles are attached to each other to form the particle trains. © 2013 Wiley Periodicals, Inc.